Learning from data in dentistry: Summary of the third annual OpenWide conference - Elsbeth Kalenderian; Kawtar Zouaidi; Jan Yeager; Janelle Urata; Alfa Yansane; Bunmi Tokede; D. Brad Rindal; Heiko Spallek; Joel White; Muhammad Walji (Wiley, 2024)
Abstract The overarching goal of the third scientific oral health symposium was to introduce the concept of a learning health system to the dental community and to identify and discuss cutting‐edge research and strategies using data for improving the quality of dental care and patient safety. Conference participants included clinically active dentists, dental researchers, quality improvement experts, informaticians, insurers, EHR vendors/developers, and members of dental professional organizations and dental service organizations. This report summarizes the main outputs of the third annual OpenWide conference held in Houston, Texas, on October 12, 2022, as an affiliated meeting of the American Dental Association (ADA) 2022 annual conference.